Intelligent technologies for interactive entertainment : 8th International Conference, INTETAIN 2016, Utrecht, The Netherlands, June 28-30, 2016, Revised selected papers /: 8th International Conference, INTETAIN 2016, Utrecht, The Netherlands, June 28-30, 2016, Revised selected papers. ([2016]) - Unknown
No abstract available